2017
DOI: 10.3390/su9020220
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Waste Generation Worldwide and Its Dependence on Socio-Economic and Environmental Factors

Abstract: This paper examines the dependence of the healthcare waste (HCW) generation rate on several social-economic and environmental parameters. Correlations were calculated between the quantities of healthcare waste generated (expressed in kg/bed/day) versus economic indices (GDP, healthcare expenditure per capita), social indices (HDI, IHDI, MPI, life expectancy, mean years of schooling, HIV prevalence, deaths due to tuberculosis and malaria, and under five mortality rate), and an environmental sustainability index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 33 publications
1
66
0
3
Order By: Relevance
“…Nevertheless, any unseparated waste from HCFs should be treated as hazardous. In addition, the terminology of HCW is interpreted differently and HCW depends on socio-economic and environmental factors, which vary among countries [50,91,92]. For example, CO 2 emissions, life expectancy, and the Human Development Index (HDI) were found to be positively correlated with HCW generation [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, any unseparated waste from HCFs should be treated as hazardous. In addition, the terminology of HCW is interpreted differently and HCW depends on socio-economic and environmental factors, which vary among countries [50,91,92]. For example, CO 2 emissions, life expectancy, and the Human Development Index (HDI) were found to be positively correlated with HCW generation [50].…”
Section: Discussionmentioning
confidence: 99%
“…According to the United Nations Development Programme [49], the Human Development Index of Sudan is 0.490 and it is ranked 165. Minoglou et al [50] reported that HCW generation depends on socio-economic and environmental factors. Therefore, all these socio-demographic and geopolitical factors have had a negative impact on the healthcare system in general and HCWM in particular, in Sudan.…”
Section: The Case Studymentioning
confidence: 99%
“…However, stronger than the aforementioned challenges for EoL strategies implementation, are the reasons why circular solutions should be adopted in this area. Minoglou et al (2017) emphasize how alarming the amount of waste produced by healthcare worldwide is, especially considering that this area is growing rapidly due to the increase of ageing populations, emerging markets and specific diseases (Landolfi et al, 2014). Furthermore, Yip et al (2015) and Fargnoli et al (2018) underline the lack of studies regarding the implementation of PSS in the medical devices area and remarked this subject as an important field for scientific investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the MoHSW estimated that approximately 4,745 metric tons were generated nationwide, with an estimated 0.41 kg per bed per day generated in the country's healthcare facilities (National Audit Office, 2014). For 2017, it was estimated that healthcare facilities generated approximately 0.75 kg per bed per day (Minoglou et al, 2017). The actual amounts are probably much higher, given that healthcare facilities often operate above full capacity.…”
Section: E-waste Generation Is Relatively Low But Informal Disposal Pmentioning
confidence: 99%